2009
DOI: 10.1177/1075547009340344
|View full text |Cite
|
Sign up to set email alerts
|

Making Space for the “Nuances of Truth”: Communication and Uncertainty at an Environmental Journalists’ Workshop

Abstract: In 2008, the Society of Environmental Journalists listed nearly 50 science or science immersion workshops for environmental journalists. Yet relatively little is known about the content of these workshops and their impact on participants. This ethnographic study, conducted at a science immersion workshop for environmental journalists, aims to fill this void in our knowledge. Relying on participant observation and depth interviews, the study suggests that such workshops are useful for participating journalists:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 17 publications
0
27
0
1
Order By: Relevance
“…Research and knowledge gaps, limitations of existing research, or contradictory findings are factors that contribute to scientific uncertainty (Schneider, 2010). Conversely, scientific certainty is increased upon confirmation of hypotheses and replications of research results (Bromme, Prenzel, and Jäger, 2014).…”
Section: How Scientists Journalists and Audiences Deal With Scientimentioning
confidence: 99%
“…Research and knowledge gaps, limitations of existing research, or contradictory findings are factors that contribute to scientific uncertainty (Schneider, 2010). Conversely, scientific certainty is increased upon confirmation of hypotheses and replications of research results (Bromme, Prenzel, and Jäger, 2014).…”
Section: How Scientists Journalists and Audiences Deal With Scientimentioning
confidence: 99%
“…Effective collaboration at the profession and team levels requires journalists to be functionally bilingual between "Sciencese" and "Publicese, " that portion of a natural language in which such terms as "ice floe" and "symmetry" are too technical to be included (Schneider, 2008). In Schneider's (Schneider, 2008) illuminating ethnographic study of a Society of Environmental Journalists' "science immersion" workshop in climate science, the most highly praised exercise involved reading peer-reviewed science papers together.…”
Section: Innumeracy Should Be the New Illiteracymentioning
confidence: 99%
“…In Schneider's (Schneider, 2008) illuminating ethnographic study of a Society of Environmental Journalists' "science immersion" workshop in climate science, the most highly praised exercise involved reading peer-reviewed science papers together. But the groups read the introduction and discussion sections.…”
Section: Innumeracy Should Be the New Illiteracymentioning
confidence: 99%
“…Qualitative evaluation of these workshops revealed that participants found them effective and the practical exercises were particularly beneficial for skill development. Similarly, Schneider [57] found that trainings for journalists can be effective, especially when these workshops include time for journalists and scientists to interact directly. Opportunities for open and reflective discussion about key science communication challenges, such as framing the concept of uncertainty, created a space for mutual learning among scientists and journalists.…”
Section: Frames As Boundary Objects and Training For Enhanced Boundarmentioning
confidence: 99%
“…We suggested that these factsheets should respond to some of the key communication issues identified in our analysis, such as providing information about relevant scientific studies to support arguments and about the potential impact of the legislation to hunting and fishing. A key next step in this effort is to develop a more extensive training program that, following Schneider's [57] example, brings scientists, journalists, and policy makers into face-to-face discussions about communication.…”
Section: Case Example: Framing and Media Training For Science-policy mentioning
confidence: 99%